Pengaruh Pembangunan Jalan Tol Layang Terhadap Kondisi Aksesibiltas Jalan A.P Pettarani - Ais Pratiwi; Murshal Manaf; Kamran Aksa (Fakultas Teknik Universitas Bosowa, 2020)
This study aims to determine how the influence of the construction of elevated toll roads on the condition of the accessibility of A.P. Pettarani. The influence of the construction of the Fly Toll Road on the accessibility condition of Jalan A.P. Pettarani, shows that some of the accessibility conditions are influenced by the variable of the elevated toll road construction. While partially the influence of the construction of the Fly Toll Road related to the implementation of construction, traffic management and the length of the toll road significantly influences the condition of A.P.Pettarani road accessibility which includes distance, travel time, transportation costs, comfort level, safety level and ease of level.